Enhancing Students' Writing Skill Through Peer-Editing Technique: A Classroom Action Research to the 11th Grade Students of SMK Negeri 1 Teluk Keramat in Academic Year 2021/2022 - Ayuda, Sri; Yuliana, Yohanes Gatot Sutapa; Rezeki, Yanti Sri; Apriliaswati, Rahayu; Surmiyati, Surmiyati (IJET (Indonesian Journal of English Teaching), 2023)
Abstract: The purpose of this study was to solve the problems found in students’ writing especially the errors in the use of authorial and secretarial aspects to the 11th grade students from OTKP major SMK Negeri 1 Teluk Keramat in the academic year 2021/2022. 18 students participated in this study. Using Classroom Action Research (CAR), this study tried to improve students’ writing skill of personal letter by the use of the peer-editing technique. The results showed that the use of the peer-editing technique successfully improved students’ writings of personal letter. It was found through the process of using the peer-editing technique, students were likely to give various types of comments and suggestions in the text structure, grammar, vocabulary, punctuation, and spelling. Through the implementation of the peer-editing technique, the students became aware of those aspects of personal letter. Finally, in the process of revision, comments from peers helped students in developing ideas and gradually produced better writing results. It was indicated by the reduction of errors found in cycle II. The improvement of students’ writing results occurred in both authorial (text structure, grammar, vocabulary) and secretarial (punctuation, spelling) aspects. Therefore, this classroom action research was successful. Students’ writing skill was improved gradually by the use of the peer-editing technique.